The role of education policy and crowdfunding in supporting the feasibility of primary schools in Indonesia - Kautsar Nasywa; Kiki Isma Indayanti (Tamalanrea: Journal of Government and Development (JGD), 2026)
The feasibility of facilities and infrastructure in primary schools is a crucial indicator for evaluating the quality of education in Indonesia. This study aims to analyze the condition of school facilities and infrastructure, identify patterns of interregional disparities, and evaluate the potential of crowdfunding as an alternative funding mechanism. A quantitative approach employing K-means clustering was used to group primary schools based on their facility and infrastructure conditions. The data used were secondary data from the Ministry of Education, Culture, Research, and Technology’s Open Data Portal, including information on educational units, student numbers, teacher qualifications, and classroom conditions. The analysis was conducted in two stages: Exploratory Data Analysis (EDA) and clustering, with evaluation using the silhouette score. The results indicate significant disparities in facilities across provinces, particularly in classroom conditions and teacher qualifications. The clustering results categorize schools into three groups based on facility and infrastructure conditions: low, medium, and high. The findings show that eastern Indonesia has the highest funding needs, suggesting that crowdfunding can serve as a strategic mechanism to support equitable improvement of primary education quality through cross-sector collaboration. This study provides practical contributions for the government, schools, and communities in designing more adaptive and sustainable education funding strategies.